1977
DOI: 10.1210/jcem-45-2-270
|View full text |Cite
|
Sign up to set email alerts
|

Subacute (de Quervain's) Thyroiditis: Association with HLA-Bw35 Antigen and Abnormalities of the Complement System, Immunoglobulins and Other Serum Proteins

Abstract: The HLA antigens in 40 patients with subacute thyroiditis were investigated. An association between subacute thyroiditis and HLA-Bw35 antigen as previously reported, was confirmed. Further immunological observations included a decrease in Serum Clq, C4 and C3 activator levels; conversely, there was an increase in serum C3, IgM, alpha1-acid glycoprotein and alpha1-antitrypsin levels. Serum IgA levels were decreased in those patients who were Bw35 negative, but were normal in the patients who were Bw-35 positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
1
3

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 10 publications
0
51
1
3
Order By: Relevance
“…A definite association between the occurrence of this disease and the presence of HLA-BW 3 5 has been demonstrated in European Caucasoids (Nyulassy et al, 1977), Chinese (Yeo et al, 1981), and Japanese patients (Kobayashi et al, 1985). In Japanese patients, the frequency of CW3 and DRW8 was also significantly higher than in the control but no increase in the frequency of A26 in subacute thyroiditis compared with normal subjects was reported (Kobayashi et al, 1985).…”
Section: Discussionmentioning
confidence: 92%
“…A definite association between the occurrence of this disease and the presence of HLA-BW 3 5 has been demonstrated in European Caucasoids (Nyulassy et al, 1977), Chinese (Yeo et al, 1981), and Japanese patients (Kobayashi et al, 1985). In Japanese patients, the frequency of CW3 and DRW8 was also significantly higher than in the control but no increase in the frequency of A26 in subacute thyroiditis compared with normal subjects was reported (Kobayashi et al, 1985).…”
Section: Discussionmentioning
confidence: 92%
“…10 The viruses implicated are Mumps, measles, adenovirus, Epstein-Barr virus, Coxsackie and influenza. 9,12,13, Typically, it presents in adults following an upper respiratory infection with fever and diffuse tender enlargement of the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…9 Individuals with human leukocyte antigen HLA-BW35 have an increased susceptibility for the development of subacute thyroiditis. 10 Studies have shown that autoimmunity is not a factor in the pathogenesis of this disease. 9 SGT is usually diagnosed clinically and therefore the cytological literature on this condition is rare.…”
mentioning
confidence: 99%
“…A case of De Quervain's thyroiditis during a-IFN therapy for HCV-related chronic hepatitis, with persisting negative anti-thyroid Abs after a-IFN therapy, has been reported [78] . The common viral infections (Coxsackie virus, mumps, Epstein-Barr virus, adenovirus, cytomegalovirus) were negative, but we found an association with HLA-Bw35 [79,80] . The patient presented the HCV, the typical HLA class Ⅰ predisposition for the thyroid disease and an exogenous accelerating factor (a-IFN therapy).…”
Section: Development Of Aitd During the A-ifn Treatment For Hcv Chronmentioning
confidence: 98%
“…The HCV genotype was 1b (20%), 2a (60%) and 3a (20%), with the distribution (1b:2a:3a) of 1:3:1 and absence of mixed genotype. It is well known that the HLA-B35, -DR3 (DRB1.03 allele) and -DR5 (DRB1.11/ HLA-DRB1.12 alleles) are commonly associated with De Quervain's thyroiditis, thyrotoxicosis/hyperthyroidism and hypothyroidism, respectively [80,[84][85][86][87][88][89][90][91][92] . Arginine at position 74 of HLA-DRB1 chain (DRB-Arg74) may permit autoAg peptides to fit into the binding pocket, to be presented more efficiently to T cells [93] .…”
Section: Development Of Aitd During the A-ifn Treatment For Hcv Chronmentioning
confidence: 99%